Is gender an important factor influencing user groups’ property rights and forestry governance?: Empirical analysis from East Africa and Latin America - Sun, Y.; Mwangi, E.; Meinzen-Dick, Ruth S. (2011)
This article explores the effects that gender composition of forest user groups has on property rights and forestry governance, based on data from 290 forest user groups in Kenya, Uganda, Bolivia, and Mexico. Findings indicate gender composition of user groups is important, but not always in the expected ways. Female-dominated groups tend to have more property rights to trees and bushes, and collect more fuelwood but less timber than do male-dominated or gender-balanced groups. Gender-balanced groups participate more in forestry decision-making and are more likely to have exclusive use of forests. Female-dominated groups participate less, sanction less and exclude less. Although policy makers and practitioners are advised to seek interventions that strengthen women’s groups by delivering information, technologies and capacity-building programs in formats that take into account women’s constraints, it is also important to gain better understanding of the dynamics of mixed-gender groups, including the nature and types of cooperation among males and females.